Projektu Pārvaldības Sistēma - Gamans, Sergejs (Latvijas Universitāte, 2011)
Sistēmas „Projektu Pārvaldības Sistēma” galvenās funkcijas ir uzglabāt informāciju par projektiem, tā dalībniekiem, aktivitātēm , ļaut ērti atlasīt šo informāciju, ka arī dod lietotajam rediģēšanas iespēju. Programmatūras galvenā īpatnība ir grafisks interfeiss , kas tika veidots pēc Windows Forms standartiem un kuru var viegli pielietot, ja ir pieredze citu Windows Forms programmatūras izmantošanas.

The systems "Project Management Tool" main functions are to save information about projects, people involved in the projects, projects activities , to make this information available for users in a convenient way and to give user opportunity to manage this data. The main feature of the system is a graphical interface, which was created in accordance with the standards of Windows Forms development and which is easy to use, having experience in other Windows Forms applications usage.
Project management tool
Keywords: Datorzinātne